Trace metal anomalies in bleached Porites coral at Meiji Reef, tropical South China Sea - 李淑 余克服 赵建新 俸月星 陈天然 (Chinese journal of oceanology and limnology, 2017)
Coral bleaching has generally been recognized as the main reason for tropical coral reef degradation, but there are few long-term records of coral bleaching events. In this study, trace metals including chromium（Cr）, copper（Cu）, molybdenum（Mo）, manganese（Mn）, lead（Pb）, tin（Sn）, titanium（Ti）, vanadium（V）, and yttrium（Y）, were analyzed in two Porites corals collected from Meiji Reef in the tropical South China Sea（SCS） to assess differences in trace metal concentrations in bleached compared with unbleached coral growth bands. Ti, V, Cr, and Mo generally showed irregular fluctuations in both corals. Bleached layers contained high concentrations of Mn, Cu, Sn, and Pb. Unbleached layers showed moderately high concentrations of Mn and Cu only. The different distribution of trace metals in Porites may be attributable to different selectivity on the basis of vital utility or toxicity. Ti, V, Cr, and Mo are discriminated against by both coral polyps and zooxanthellae, but Mn, Cu, Sn, and Pb are accumulated by zooxanthellae and only Mn and Cu are accumulated by polyps as essential elements. The marked increase in Cu, Mn, Pb, and Sn are associated with bleaching processes, including mucus secretion, tissue retraction, and zooxanthellae expulsion and occlusion. Variation in these trace elements within the coral skeleton can be used as potential tracers of short-lived bleaching events.